2021
DOI: 10.1186/s13293-021-00381-4
|View full text |Cite
|
Sign up to set email alerts
|

A cross-cohort analysis of autosomal DNA methylation sex differences in the term placenta

Abstract: Background Human placental DNA methylation (DNAme) data is a valuable resource for studying sex differences during gestation, as DNAme profiles after delivery reflect the cumulative effects of gene expression patterns and exposures across gestation. Here, we present an analysis of sex differences in autosomal DNAme in the uncomplicated term placenta (n = 343) using the Illumina 450K array. Results At a false discovery rate < 0.05 and a mean sex … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
26
4

Year Published

2022
2022
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 29 publications
(37 citation statements)
references
References 77 publications
7
26
4
Order By: Relevance
“…Though these studies varied in their methodological approach and probe filtering strategies, this result supports the conclusion that the majority of differentially methylated sites identified herein are placenta-specific. Consistent with this notion, our results did overlap well with a previous study 43 of full term placenta DNAm differences by fetal sex, capturing 146 of the 166 CpG sites identified in this study.
Figure 2 Single site discovery in full term placenta samples.
…”
Section: Resultssupporting
confidence: 92%
“…Though these studies varied in their methodological approach and probe filtering strategies, this result supports the conclusion that the majority of differentially methylated sites identified herein are placenta-specific. Consistent with this notion, our results did overlap well with a previous study 43 of full term placenta DNAm differences by fetal sex, capturing 146 of the 166 CpG sites identified in this study.
Figure 2 Single site discovery in full term placenta samples.
…”
Section: Resultssupporting
confidence: 92%
“…The extent of methylation at all four sites was higher in placentas of male than of female neonates. This observation is consistent with a recent study showing that most autosomal loci with sex-dependent DNA methylation in human term placenta are more highly methylated in male than in female placentas [ 65 ].…”
Section: Discussionsupporting
confidence: 93%
“…Consistent with this, we were able to replicate 75% of our saDMPs identified in our validation data set in our discovery data set. Moreover, we found that 73% of the saDMPs we identified in this study were also identified by Inkster and colleagues [ 27 ], whom also applied effect size cut offs, demonstrating the reproducibility and robustness of our catalogue of saDMPs.…”
Section: Discussionsupporting
confidence: 75%
“…We also additionally checked the overlap between our saDMPs identified in blood with those identified in other tissues (Table 2 ). Interestingly, we observe a 73% overlap with sex-associated sites identified in placenta by Inkster et al [ 27 ] and a 35% overlap with sex-associated sites identified in post-mortem prefrontal cortex [ 66 ]. The existence of this overlap between different tissues shows that a portion of these saDMPs identified are conserved across tissues, and that some are tissue specific.…”
Section: Discussionmentioning
confidence: 54%
See 1 more Smart Citation